GPX1 genetic variants rs2107819200 and rs1575633487 in disease status and tyrosine kinase inhibitor response in chronic myeloid leukemia patients - H. Al-Nayyar; K. Ben-Mahrez (Regulatory Mechanisms in Biosystems, 2025)
Chronic myeloid leukemia (CML) is a hematological malignancy driven by the BCR:ABL1 fusion gene. Oxidative stress is implicated in CML progression and treatment resistance. Glutathione peroxidase (GPX1), a key antioxidant enzyme, helps modulate oxidative stress. Genetic variations in the GPX1 gene may alter enzyme function and affect disease risk or treatment response. The o bjective of this article is to investigate the association of GPX1 single nucleotide polymorphisms (SNPs) rs2107819200, and rs1575633487 with CML altering susceptibility and response to tyrosine kinase inhibitor (TKI) treatment in Iraqi patients. A case-control study was conducted including 120 CML patients (20 newly diagnosed and 100 under TKI treatments), who were diagnosed based on detection of the BCR:ABL1 fusion gene by reverse transcription polymerase chain reaction (RT-PCR), and 60 healthy controls. Genomic DNA was extracted from peripheral blood and genotyped for the two SNPs rs2107819200 and rs1575633487 using conventional PCR followed by Sanger sequencing. Statistical analyses were performed, by calculating the odds ratio (OR) with a 95% confidence interval (CI) and P-value, to assess genotype frequencies and the associations with susceptibility of CML and treatment status. In the overall analysis, no significant association was found between both SNP and general CML susceptibility. However, subgroup analysis revealed a strong association between the rs1575633487 TG genotype and newly diagnosed disease (45%) compared to treated patients (8%) (OR = 11.3; 95% CI: 2.54–50.5; P = 0.001). Similarly, for rs2107819200, the CG genotype was significantly more frequent in newly diagnosed patients (25%) versus treated patients (11%) (OR = 3.00; 95% CI: 1.66–13.8; P = 0.001). The CC genotype, while most prev a lent overall, appeared more commonly in treated patients (79%) than in newly diagnosed patients (55%), suggesting possible genotype shifts with therapy. While no associations were found between these two GPX1 polymorphisms and general CML risk, both rs1575633487 TG and rs2107819200 CG genotypes were significantly associated with newly diagnosed disease, suggesting a potential role in early-phase pathogenesis or oxidative stress regulation. These findings support their utility as candidate biomarkers for early disease status or therapeutic monitoring and warrant further validation through large-scale, ethnically diverse studies and functional analyses.